Seed Production and Seed Sources of Organic Vegetables - Jennifer Bonina; Daniel J. Cantliffe (EDIS)
The organic vegetable industry is flourishing due to consumers preference for organically grown produce over traditionally produced vegetables. As a result, an increase in the variety and selection of many vegetables in retail supermarkets and restaurants throughout the United States has occurred recently. With the new regulation (October 2000) requiring organic seed sources for organically labeled vegetables, many organic growers are searching for certified organic seed. Smaller seed companies have produced the majority of organically produced seed to date. The commercial seed sector is starting to provide a more diverse selection of cultivars, yet there are still many hybrids that are not yet available. For growers in Florida, there is opportunity to produce organic, though it is not widely practiced. This report serves as a guide to organic seed production in Florida. This document is HS981, one of a series of the Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: July 2004.